Antiferromagnetic Alkali Metal Oxohydroxoferrates(III) with Correlated Hydrogen Bonding Systems - Albrecht, Ralf; Hunger, Jens; Hoelzel, Markus; Block, Theresa; Poettgen, Rainer; Doert, Thomas; Ruck, Michael (ChemistryOpen, 2019)
The oxohydroxoferrates(III) A2[Fe2O3(OH)2] (A=K, Rb, Cs) were synthesized under hydroflux conditions. Approximately equimolar mixtures of the alkali metal hydroxides and water were reacted with Fe(NO3)3 ⋅ 9H2O at about 200 °C. The product formation depends on the hydroxide concentration, therefore also other reaction products, such as KFeO2, K2−x[Fe4O7−x(OH)x] or α-Fe2O3, are obtained. The crystal structures of the oxohydroxoferrates(III) A2[Fe2O3(OH)2] follow the same structural principle, yet differ in their layer stacking or/and their hydrogen bonding systems depending on A and temperature. In the resulting four different orthorhombic structure types, [FeO3OH]4− tetrahedra share their oxide corners to create folded ∞ 2Fe2O3(OH)2]2− layers. The terminal hydroxide ligands form hydrogen bonds between and/or within the layers. The positions of the hydrogen atoms in these networks are correlated. The A+ cations are located between the folded anionic layers as well as in their trenches. Under reaction conditions, the potassium compound crystallizes in the space group Cmce (Pearson symbol oC88), showing a bimodal disorder of the hydrogen atoms in hydrogen bridges. In a virtually hysteresis-less first-order transition at 340(2) K, the structure slightly distorts into the room-temperature modification with the subgroup Pbca (oP88), and the hydrogen atoms order. The rubidium and caesium compounds are isostructural to each other but not to the potassium compound, and are always obtained as mixtures of two modifications with space groups Cmce (oC88′) and Immb (oI88). Upon heating, the oxohydroxoferrates decompose into their anhydrides AFeO2 and water. The type of hydrogen bonding network influences the decomposition temperature, the structure and the morphology of the crystals. Despite the presence of iron(III), which was confirmed by 57Fe-Mössbauer spectroscopy, K2[Fe2O3(OH)2] is diamagnetic in the investigated temperature range between 1.8 and 300 K. Neutron diffraction revealed strong antiferromagnetic coupling of the magnetic moments, which are inverted in neighboring tetrahedra.
CRIS-Team Scopus Importer:2022-04-14
Keywords: crystal structure; hydroflux; magnetic structure; oxohydroxoferrates; thermal analysis